Exploring depth psychology and the female self : feminist themes from somewhere - Gardner, Leslie, 1949-; Miller, Catriona, 1968- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Exploring Depth Psychology and the Female Self: Feminist Themes from Somewhere presents a Jungian take on modern feminism, offering an international assessment with a dynamic political edge which includes perspectives from both clinicians and academics. Presented in three parts, this unique collection explores how the fields of gender and politics have influenced each other, how myth and storytelling craft feminist narratives and how public discussion can amplify feminist theory. The contributions include some which are traditionally theoretical in tone, and some which are uniquely personal, but all work to encounter the female self as an active entity. The book as a whole offers a multi-faceted and interdisciplinary approach to feminism and feminist issues from contemporary voices around the world, as well as a critique of Jung's essentialist notion of the feminine. Exploring Depth Psychology and the Female Self will offer insightful perspectives to academics and students of Jungian and post-Jungian studies, gender studies and politics. It will also be of great interest to Jungian analysts and psychotherapists, and analytical psychologists.
Rowland, Preface. Gardner, Introduction. Part 1: Gender in Politics/Politics in Gender. Flowers, Empowered by myth. Tuley, The jouissance of 'nasty women'. Chrzescijanska, The concept of 'therapeutic space' as maternal space in depth psychology -- a critique. Auestad, Sexual counter-revolution. Goss, Gender difference. Part 2: Stories: Ancient and contemporary. Miller, Becoming queen. Dawson, Gender and the political Antigone. Sengupta, Earth, ecology and the feminine. Certa-Narcida, The modern ancients. Wang, The Peony Pavilion. Buchanan, Dynamic growth and infinite feminine potential in The Walking Dead. Part 3: Voices. Zaphiriou-Zarifi, Women in war zones. Maher, The role of the grandmother. Gray, Alternative visions -- polysemy/art. Gardner, Let's talk about our mothers. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Women -- Psychology; Feminism; Jungian psychology; PSYCHOLOGY / Movements / Jungian; SOCIAL SCIENCE / Gender Studies